Anaerobic bacteria and herpes simplex virus in genital ulceration. - Masfari, A N (1985)
Of 91 patients with genital ulceration, herpes simplex virus was isolated from 52 (57%) and Haemophilus ducreyi from 12 (13%); none had syphilis. The difference in incidence of other aerobes in patients and controls was not significant. Anaerobes, predominantly Bacteroides spp, were isolated from a large proportion (77%) of men and women patients with ulcers but from few control men. The most common anaerobic species were B asaccharolyticus and B ureolyticus, with fewer isolates of the melaninogenicus/oralis group. The bacterial flora of herpetic and non-herpetic ulcers were similar, but Candida albicans was isolated significantly more often from non-herpetic ulcers. Anaerobic bacteria may contribute to the pathogenesis of genital ulcers.